Effectiveness of home-based cardiac telerehabilitation as an alternative to Phase 2 cardiac rehabilitation of coronary heart disease: a systematic review and meta-analysis. - Ramachandran, Hadassah Joann (Oxford University Press (OUP), 2021)
10.1093/eurjpc/zwab106